Dielectric and magnetic properties of NiZn-polypropylene and CoZn-polypropylene ferrite composite - Tan, Foo Khoon (2011)
Polymer-clay composites exhibit more interesting and improved mechanical, thermal, electrical, optical and pharmaceutical properties as compared to the pure polymer. Guided and motivated by this observation, the main objective of this project is to study the dielectric and magnetic properties of ferrite-polypropylene composites. The effects of different chemical composition of ferrite and different composition of ferrite added to the matrix were investigated. The fillers, MexZn1-xFe2O4 (where Me=Ni, Co; x=0.1, 0.2 and 0.3) were prepared by the conventional solid state method. Different compositions of filler were doped into the polypropylene (PP) and blended to produce ferrite-PP composites. For characterization, X-ray diffraction (XRD) was used to determine the crystalline structure while field emission scanning electron microscopy (FESEM) was used to analyze the microstructure of the ferrites. The dielectric properties were measured using an HP 4284A Precision LCR Meter from 20 Hz to 1 MHz at room temperature. An HP4291B RF Impedance Analyzer was used to measure the dielectric properties and magnetic properties of the samples from 1 MHz to 1.8 GHz at room temperature. From the XRD analysis, it showed that the filler and PP underwent no unwanted reaction during blending process. According to the FESEM images, the average grain diameters of ferrites increased with increasing Zn content in ferrite. The composites with 30 wt% of ferrite added exhibit the highest relative dielectric constant,E' which are 3.44 at 1 kHz and 2.78 at 100 MHz for i0.3Zn0.7Fe2O4-PP composite. The existence of ferrite may take part in compensating the dipole moment of PP. Hence, the E' of 5 wt% - 10 wt% of ferrite composite is lower than pure PP due to the small amount of ferrite (moderate dielectric properties) added which do not give a significant contribution toward PP – based composite. Therefore, a significant improvement on the E' of the composites can be obtained with the addition of ferrite with more than 10 wt%. The addition of ferrite shifted the dielectric loss peak to lower frequencies. A composite with high relative dielectric loss, u" thus it can be utilized as electromagnetic wave absorbing material. By varying the weight ratio of ferrite, the composite can be tailored as an absorbing material at a desired frequency between 10 kHz to 300 kHz. However, the composites do not have significantly improved relative real permeability, u' due to the discontinuity of magnetic flux. 30 wt% of Co0.3Zn0.7Fe2O4 – PP composite has the highest U' which is 1.94 at 50 MHz. As summary, the reinforcement of polymer with filler can enhance the dielectric and magnetic properties of the polymer composites. According to the effective medium theory, the high permittivity or high permeability of the polymer based composites can be obtained by putting the high permittivity or high permeability ceramic particles into the polymer matrices. Therefore, 30 wt% of ferrite-polypropylene composites are given the highest E' and u' among other composites at 20 Hz – 1 MHz and 1 MHz – 1.8 GHz.